Rights of underage patients - Akhmetianova, Zamira Asrarovna; Garaeva, Geliusa Khadievna; Nizamieva, Olga Nikolaevna; Khamidullina, Farda Ildarovna (Linguistics and Culture Review, 2021)
The right of Russian citizens to their health protection is enshrined in the Constitution of the Russian Federation. However, there are peculiarities of the exercise of this right by a minor category of patients. The article analyzes the legal status of a minor patient, considers his social and individual rights in medical care. The peculiarities of the exercise of the child’s right to information about the state of his health are revealed, the aspects of deciding on consent or refusal from medical care are considered. Given the fact that minor patients do not have full civil legal capacity, i.e. they cannot be responsible for their health and are not able to protect themselves, the article examines the relationship between the child’s right to give his consent to medical intervention with the volume of civil legal capacity, as well as the conditions for the participation of a minor in contractual relations in the field of health care. The authors analyzed peculiarities of the exercise of rights by certain categories of minor patients: those who suffer from mental disorders, orphans and children left without parental care, minors, drug addicts, etc.